PENGARUH PERTUMBUHAN SIMPANAN DANA PIHAK KETIGA DAN PEMBIAYAAN TERHADAP LABA OPERASIONAL - Fatimah, Siti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
PT BPRS Baktimakmur Indah is one of alternative banking institutions that is used to expand theprovision of funds that is needed by the community by using syariah principle in its management. Third-partyfunds deposit is the largest source of funding for banking whereas financing is one of the sources of income ofBPRS which has been obtained from profit sharing/margin. The purpose of this research is to test the influence ofthird-party funds deposit and financing to the operating profit of PT BPR Syariâah Baktimakmur Indah from2008 to 2013. The data collection is performed by using documentation technique whereas the data analysismethod is carried out by using descriptive analysis, statistics analysis and multiple linear regressions analysis.The SPSS program version 16 is used in conducting data processing. The result of the research shows that (1)savings has no influence to the operating profit. (2) Deposits have no influence to the operating profit. (3)Financing has no influence to the operating profit.Keywords: Savings, Deposits, Financing, and Operating Profit